From Delivery Delays to AI-Mediated Escalation Failures: A BERTopic Analysis of Complaints About Risk and Trust in E-Commerce Marketplaces (2019-2025) - Saglam, Munise Hayrun (MDPI, 2026)
Automated customer service and algorithmic governance are common in digital marketplaces, yet trust can erode when logistics, refunds, and escalation fail. Complaint-based risk and trust narratives in Turkey's e-commerce marketplaces are analyzed for January 2019-December 2025 using 118,173 de-identified Turkish and English texts from & Scedil;ikayetvar, a leading Turkish online consumer-complaint portal, and reviews of official marketplace apps on Google Play and the Apple App Store. BERTopic is implemented in Python with multilingual transformer embeddings, UMAP, HDBSCAN, and c-TF-IDF representations. The selected model identifies 35 micro-topics grouped into five macro-themes: fulfillment disruptions, remediation frictions, product-integrity risks, escalation failures, and governance threats. Monthly probability-weighted prevalence is estimated, and marketplace differences are evaluated with divergence measures, permutation tests, and multinomial regression controlling for time and language. Changepoint tests indicate a shift toward fulfillment grievances in April 2020, rising governance threats from June 2022, and increasing escalation failures linked to automated support from February 2023. These patterns suggest that barriers to human escalation convert operational incidents into platform-level trust judgments, offering monitoring signals for service recovery, marketplace governance, and AI oversight. By isolating escalation failures as a distinct complaint domain, the study links service automation to procedural justice mechanisms that translate operational breakdowns into platform-level trust and risk judgments.
Keywords: e-commerce; consumer complaints; trust; perceived risk; BERTopic; topic modeling; AI customer service; procedural justice; platform governance; multilingual text mining; ELECTRONIC COMMERCE; SERVICE RECOVERY; SUPPLY CHAIN; ONLINE; PRIVACY; JUSTICE; MODEL; PERSPECTIVES; INTENTION; Business & Economics